Multiple nash equilibriums and evaluation of strategies. New application of MCDM methods - Hashemkhani Zolfani, Sarfaraz; Maknoon, Reza; Zavadskas, Edmundas Kazimieras (Journal of Business Economics and Management, 2014)
There are two different approaches in this study with different implications. The first approach and the main aim of this study is a methodological framework. There are different frameworks in solving game theory topics involving at least two Nash Equilibriums. This study presents a new framework for developing this part of game theory with MCDM framework. The authors believe that at least there is a perspective or paradigm behind each game theory topic, leading to the development of strategies accordingly. For this purpose a hybrid MCDM method based on SWARA-WASPAS is applied in the process of research for evaluating the strategies. The general topic of this research is in supply chain management field. This research also focuses on this issue and implies extend of the complication involved. An additional focus in the present paper is on defining a game. This research addresses developing strategies from only stable strategies to both normal and dynamic strategies. The topic is established to find the best mixed strategy considering current international and economical position of Iran against complicated international relations’ issues and specially sanction.